Penyuluhan Dan Parenting Edukasi Sex Pada Anak Usia Dini Dan Remaja Perspektif Islam - Anwar, Rosyida Nurul; Alfina, Alisa (Jurnal Pendidikan Tambusai, 2021)
In general, there are still those who talk about sex with children because it is still taboo. This response developed in the wider community. Sex education should be introduced to early childhood and adolescents so that children can know and see about sex, its benefits, and dangers. Real steps in providing sex education to early childhood and adolescents by parents are contained in community service activities which are carried out for parents who are members of the Al Hidayah group of majlis taklim, Sidomulyo Village. The participants were attended by mothers as much as 91% and fathers as much as 9% with children aged 0-24 years. The method of implementation is done by presenting it through lectures and discussions. The post-test results showed an increase in the participants' understanding. Judging from the usefulness of the material the yield is 90% very useful. In terms of the quality of the speakers, it is 100% of the assessment of the speakers in terms of knowledge and delivery. Overall, the participants had high enthusiasm as evidenced by following the activities from the beginning to the end of the event.